Case Report: Respiratory outcome in a preterm infant following previable rupture of membranes and persistent oligohydramnios - Subramanian, Akila; Zhi, Ong Kai; Pugalenthi, Arun Kumar; Rajadurai, Victor Samuel; Tan, Lay Kok; Chandran, Suresh (Frontiers in Pediatrics, 2025)
Mid-trimester preterm premature rupture of membranes is a rare complication of pregnancy associated with significant maternal and fetal risks. The ensuing prolonged oligohydramnios can lead to fetal pulmonary hypoplasia. In addition, there is an increased risk of miscarriage, preterm birth, and chorioamnionitis, contributing to septic morbidity in the mother–baby dyad. This case report describes the management and outcomes of an infant born at 32 weeks following the rupture of membranes at 16 weeks of gestation, resulting in severe oligohydramnios. Soon after birth, the infant had respiratory compromise, requiring high-frequency oscillatory ventilation and nitric oxide. Despite the initial poor prognosis, the infant remained stable with various ventilation modalities managed by a multidisciplinary team. He was discharged home after 108 days in the hospital and remained on non-invasive ventilatory support until 8 months of age while the home care and hospital specialty teams monitored him. The favorable respiratory outcome of this case is a rarity for cases with similar clinical circumstances, in which the managing team counsels parents about poor fetal outcomes and many proceed to terminate the pregnancies. In this reported case, we highlight the importance of multidisciplinary and interprofessional team management from antepartum monitoring and planning delivery time to subsequent short- and long-term postnatal care involving maternal-fetal medicine specialists, neonatologists, pediatric cardiology and respiratory specialists, and home care teams.